Low baseline neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios predict increased overall survival in locally recurrent rectal cancer despite R1 margins. Issue 7 (July 2022) - Daveri, Elena; Sorrentino, Luca; Lalli, Luca; Guaglio, Marcello; Battaglia, Luigi; Cattaneo, Laura; Sabella, Giovanna; Milione, Massimo; Rivoltini, Licia; Cosimelli, Maurizio; Belli, Filiberto
Abstract: Background: Prognostic features in locally recurrent rectal cancer (LRRC), beyond R0 surgery, are unknown. Aims: Aim of the present study was to evaluate the prognostic role of peripheral immune estimators, such as neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), on survival outcomes in LRRC patients. Methods: 184 LRRC patients treated at the National Cancer Institute of Milan (Italy) were included. Optimal cut-off values for NLR and PLR were determined. Kaplan-Meier curves and multivariate Cox analyses were used to assess the 5-yr overall survival (OS) according to NLR and PLR, also considering margins status. Results: NLR >3.9 (hazard ratio [HR] 3.96, P  = 0.049), PLR >275 (HR 5.39, P  = 0.002) and size on imaging (HR 1.36, P  = 0.044) were associated to worse OS. R+ patients with NLR >3.9 showed a significantly lower 5-yr OS compared to NLR ≤3.9 (13.5% vs. 36.7%, P  < 0.0001). Also PLR >275 was related with a lower 5-yr OS compared to PLR ≤275 in R+ patients (6.4% vs. 36.8%, P  = 0.0003). Conversely, NLR and PLR were irrelevant in case of R0 surgery. Conclusion: NLR and PLR predict 5-yr OS in LRRC, also identifying a subset of R+ patients with a similar expected survival compared to R0 cases.